Sediment echosounder raw data (Innomar SES-2000 working area dataset) of RV ALKOR during cruise AL591, Eckernförde Bay - Kaul, Norbert; Lohrberg, Arne; Plötz, Aline (PANGAEA, 2025)
Around Mittelgrund, a sandbank of glacial origin in the western Baltic Sea, subbottom profiles were conducted with the German research vessel "Alkor" on the cruise AL591 in April 2023. Subbottom profiles were collected using the sediment echosounder SES-2000 from Innomar. The system was operated in a single frequency mode of 6 kHz with a vessel speed below 5 knots. This dataset contains the raw data (*.raw), the envelope (*.ses), converted for Kingdom or similar (*.sgy), navigation (UTM_X, UTM_Y, shot point, date, time) (*.txt), the motion (*motion.txt) and header information (*Header.txt) for two profiles. The raw data are stored in UTM zone 32U. - Profile east – west (20230411): A profile south of 'Mittelgrund' crosses the transition between muddy sediments with and without acoustic disturbance. - Profile north - south (20230412): A transect at the western margin of 'Mittelgrund', with the transition from sandy to muddy sediments.
Keywords: Baltic Sea; sediment echosounder